Kajian Pengurusan Fasiliti Landskap Di Bandar Penggaram, Batu Pahat - Salahudin, Nurazyani Haifaa; Shareh Musa, Sharifah Meryam; Kassim, Narimah; Mohd Noh, Hamidun; Zainal, Rozlin (Research in Management of Technology and Business, 2021)
Landscape facility management is an important aspect to ensure that the landscape is in good condition while creating public well-being in line with the original purpose of its development. However, landscape management in our country still does not reach the desired level. Therefore, this study was conducted to study the management of landscape facilities in Bandar Penggaram, Batu Pahat. The objective of the study is to identify landscape management methods by the Batu Pahat Municipal Council (MPBP) in improving the quality of landscape maintenance in Bandar Penggaram and to study the level of public satisfaction with the management of landscape facilities provided by the MPBP. Research methodology uses field survey methods, interviews and questionnaires. The questionnaire involved 105 respondents, namely users at three selected stations in Bandar Penggaram, which are BP Walk, Dataran Penggaram and Taman Rekreasi Tasik Y. Interviews were conducted with MPBP and maintenance contractors who manage landscape facilities in the area. The results show that the landscape maintenance method used is maintenance on a daily and periodic basis. Maintenance is done according to the type of landscape based on the methods that have been set. In addition, the results of the study found that the respondents were satisfied with the maintenance of grass cutting on a scheduled basis, which is a mean value of 4.03. The trees planted should also be suitable and meet local needs, the majority of respondents agree with this statement. Providing a clear and easy-to-understand information board is also important. This statement was agreed by the respondents by recording a mean value of 4.04. Landscape maintenance in Bandar Penggaram requires improvements in terms of playground facilities to provide comfort to users. In conclusion, systematic landscape management is important to ensure visitor satisfaction in line with current needs.